Membangun Pemahaman Siswa tentang Nilai Gizi Melalui Edukasi Literasi Label Pangan - Putri Nur Aini; Ayik Mirayanti Mandagi; Rifka Pramudia Wardani; Nurul Agustina Kurniawati; Rina Pertiwi; Afan Alfayad (FORIKES, 2024)
Lack of knowledge of adolescents about consumption patterns causes inappropriate consumption patterns. Changes in increasing knowledge about food labels can be attempted through education. This study aimed to determine the increase in students' knowledge after an intervention in the form of education on reading food labels. The design of this study was one group pretest-posttest. The subjects of this study were 44 intra-school student organization administrator of the Madrasah Aliyah Muhammadiyah 01 Jember. The intervention was carried out using lecture and discussion methods, and supplemented with exercises. The media used were posters and Power Point presentations. Furthermore, a comparative analysis of students' knowledge levels between before and after education was carried out, using a paired samples t-test. The results of the analysis showed that the average level of knowledge about reading food labels before the intervention was given was 40.54. After the intervention, the average increased to 60.68. The p-value of the t-test was 0.000, so it is interpreted that there is a difference in students' knowledge levels between before and after the intervention. Furthermore, it is concluded that food label literacy education is effective in increasing students' knowledge about how to read nutritional information on packaged food labels.Keywords: students; nutritional value; food labels; knowledge ABSTRAK Kurangnya pengetahuan remaja tentang pola konsumsi menyebabkan terjadinya pola konsumsi yang kurang tepat. Perubahan peningkatan pengetahuan mengenai label pangan dapat diusahakan melalui edukasi. Penelitian ini bertujuan untuk mengetahui peningkatan pengetahuan siswa setelah dilakukan intervensi berupa edukasi pembacaan label pangan. Desain penelitian ini adalah one group pretest-postest. Subjek penelitian ini adalah 44 pengurus Organisasi Siswa Intra Sekolah Madrasah Aliyah Muhammadiyah 01 Jember. Intervensi dilakukan dengan metode ceramah, diskusi, dan dilengkapi dengan latihan. Media yang digunakan poster dan prsentasi Power Point. Selanjutnya dilakukan analisis perbandingan tingkat pengetahuan siswa antara sebelum dan sesudah edukasi, menggunakan paired samples t-test. Hasil analisis menunjukkan bahwa rerata tingkat pengetahuan tentang pembacaan label pangan sebelum diberikan intervensi adalah 40,54. Setelah intervensi, rerata meningkat menjadi 60,68. Nilai p dari uji t adalah 0,000, sehingga ditafsirkan bahwa ada perbedaan tingkat pengetahuan siswa antara sebelum dan sesudah dilakukan intervensi. Selanjutnya disimpulkan bahwa edukasi literasi label pangan efektif untuk meningkatkan pengetahuan siswa tentang cara membaca informasi nilai gizi pada label pangan kemasan.Kata kunci: siswa; nilai gizi; label pangan; pengetahuan